INDIGENOUS CRIME CONTROL IN SELECTED COMMUNITIES OF IJEBU NORTH LOCAL GOVERNMENT AREA OF OGUN STATE - OLANIPEKUN, Lateef, O (Journals Park Publishing, 2022)
This examined “indigenous crime control in selected communities of Ijebu North Local Government Area of Ogun State with the objectives of examining the process indigenous crime control, investigate the agents of indigenous crime control, examine the mechanisms of indigenous crime investigation and control and examining the patterns of indigenous security maintenance, crime prevention, and other law enforcement. The study adopted the descriptive survey research and obtained data through a quantitative instrument from of one hundred and nine (109) respondents from five (5) selected communities. The data generated were checked, cleaned and analysed using the Statistical Package for Social Sciences (SPSS). The bivariate analysis was captured using the Chi-square test which focused on depicting the relationships that exists among the variables or square or Weight Index and Relative Perception Index (RPI). Findings revealed that Indigenous crime controls agencies have significant effect on crime control in the community and their intervention has drastically reduce crime rates using Vigilantes, Institutions of deities, Secret societies, Divination, Invocation of the gods and Trial by Ordeal as good and effective agents and mechanisms for indigenous crime control. The study concluded that anti-terror policing tactics, increasing para-militarism, procurement of expensive high-tech gadgets and re-orientating the security agencies to work better with the public will enhance the detection of crime and extremism. Therefore, this study recommended that, the indigenous crime control agency which is fast becoming popular amongst developed and developing communities in Nigeria be recognized by the Nigerian government and made to partner with the government in carrying-out policing activities nationwide.
Keywords: Crime; Vigilante; Divination